The Construction of Personal Identity through Internalizing Societal Norms Case Study: The Protagonist in Kurt Vonnegut’s The Sirens of Titan - Bendouma ,Noureddine; Touhami, Ibtissam (Faculty of Letters and Foreign Languages Department of English, 2018)
This study aims to recognize the factors which are responsible for constructing a person’s identity. It also attempts to tackle the problem of personal identity from a different perspective, which is the construction of personal identity throughout the interaction that one is exposed to within a society, not neglecting the ability of a person to reason, criticize and take matters on one’s own hands. Consequently, this study aims to investigate whether or not social norms are the reference to the identity of a person in relation to Kurt Vonnegut’s work: The Sirens of Titan, and specifically the protagonist of the novel, Malachi Constant/Unk, whom, throughout analysis, will either prove to have his identity constructed by external factors (i.e. Social norms) or by other factors which seek to be explained